Bibliometric Analysis of Studies on Academic Burnout in Students - Bali, Onur; Kaya, Alican; Sata, Mehmet; Allen, Kelly-Ann (Journal of University Teaching and Learning Practice, 2024)
Academic burnout is characterised by emotional exhaustion, depersonalisation, and diminished personal accomplishment amongst students. Despite its rising prominence in recent discussions, there remains a lack of systematic reviews encapsulating the extensive literature on academic burnout. This bibliometric study aims to systematically review the literature and determine trends in academic burnout research. A total of 805 studies on academic burnout were retrieved from the WoS database and 570 articles meeting the selection criteria were analysed. The distribution of articles was analysed based on categories, publication years, and originating countries. Additionally, pertinent topics, journals, authors, and patterns of global and local citations were examined. Our analysis revealed a notable increase in articles on academic burnout in recent years. Leading contributors in terms of publications include China, the USA, and Finland. Recently, themes such as "Covid-19", "depression", "resilience", "classroom enjoyment", and specific demographics like "medical students" and "working students" have been frequently associated with academic burnout research. This research reveals the multifaceted structure of academic burnout. As a result, educational professionals can incorporate the multifaceted structure resulting from this research into programs designed to reduce academic burnout.